2019
DOI: 10.4236/ojg.2019.95018
|View full text |Cite
|
Sign up to set email alerts
|

Upper Sun River Drainage Basin Origin Determined by Topographic Map Interpretation Techniques: Lewis and Clark and Teton Counties, Montana, USA

Abstract: A new and fundamentally different regional geomorphology paradigm in which massive south-and southeast-oriented meltwater floods flowed across the entire Missouri River drainage basin is tested by interpreting detailed topographic maps of the Montana upper Sun River drainage basin region by trying to explain origins of previously unexplained or poorly explained erosional landforms located upstream from Sun River Canyon (which cuts across Montana's north-to-south oriented Sawtooth Range). Mountain passes, throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Another paper [25] interprets topographic map evidence to show that immense south-oriented floods eroded mountain passes now crossing continental divide segments surrounding the Boulder River drainage basin (located to the east of the Clark Fork River headwaters seen in Figure 1). And a third paper [26] interprets topographic map evidence to show that immense southoriented floods eroded mountain passes crossing continental divide segments surrounding the upper Sun River drainage basin (located in Figure 1 to the west of where the Missouri River turns from flowing in a northwest direction to flow in a northeast direction).…”
Section: Previous Literaturementioning
confidence: 99%
“…Another paper [25] interprets topographic map evidence to show that immense south-oriented floods eroded mountain passes now crossing continental divide segments surrounding the Boulder River drainage basin (located to the east of the Clark Fork River headwaters seen in Figure 1). And a third paper [26] interprets topographic map evidence to show that immense southoriented floods eroded mountain passes crossing continental divide segments surrounding the upper Sun River drainage basin (located in Figure 1 to the west of where the Missouri River turns from flowing in a northwest direction to flow in a northeast direction).…”
Section: Previous Literaturementioning
confidence: 99%
“…Several such papers demonstrate how topographic map evidence indicates north-oriented valleys eroded headward from a continental ice sheet location (where ice sheet melting was opening up space at the deep "hole's" southern end) to capture massive southeast-oriented ice-marginal floods [18] [19] [20]. Other papers describe topographic map evidence demonstrating how massive floods flowed across a rising Laramie Range [21] and a rising Black Hills uplift [22] and carved what is today a northern Montana east-west continental divide segment [23].…”
Section: Previous Workmentioning
confidence: 99%
“…As a bulge within the Missouri River drainage basin near, but not on the deep "hole's" southwest rim, the new paradigm requires southor southeast-oriented melt water floods to have flowed across what must have been a rising Bighorn Mountain range. Previously published new paradigm papers among other things demonstrate how detailed topographic map evidence suggests large south-and southeast-oriented floods flowed across a rising Wyoming-South Dakota Black Hills upland (Clausen, 2018b), a rising Wyoming Laramie Range (Clausen, 2018c), rising Montana Lewis and Clark and Sawtooth Ranges (Clausen, 2019), a rising Montana Boulder Batholith region (Clausen, 2017a), rising Montana Beaverhead, Centennial, Pioneer, and Anaconda Mountain ranges (Clausen 2017b) and the eastern Powder River Basin (Clausen, 2018d) and also demonstrate how the southeast Montana north-oriented Powder River valley eroded headward across massive southeast-oriented floods (Clausen, 2018e). The study reported here seeks to determine whether detailed topographic map evidence in the high elevation southern Bighorn Mountains region can be interpreted in similar ways.…”
Section: Previous Workmentioning
confidence: 99%